Analysis of early vigour in twenty modern cultivars of bread wheat (Triticum aestivum L.) - Maydup, Maria Luján (2012)
Fast development of seedling leaf area is a relevant trait in order to increase early resource acquisition. The use of semi-dwarf genotypes of wheat has decreased early vigour of modern cultivars. We studied early vigour of 20 cultivars cropped in Argentina, and our main objectives were: (i) to analyse the genotypic variability in early vigour; (ii) to study morphological traits that can be good indicators of early vigour, such as seed mass, leaf width, and specific leaf area; and (iii) to determine whether increased dry mass allocation to roots impacts negatively on early vigour. Experiments with non-size-selected and size-selected seeds were carried out in a greenhouse. A field trial was also conducted in order to test the reliability of the greenhouse results. Seeds mass was the main parameter related to early vigour. However, results from the experiment with seeds selected by size (45-50mg seed-1) showed that seed mass per se only partially explains early vigour, since a significant coefficient of determination was observed between the seedling leaf area of each cultivar in both experiments (i.e. with randomly chosen or size-selected seeds). We observed a high coefficient of determination between net assimilation rate and changes in the ranking of early vigour of the cultivars with time after transplant. Root biomass was positively correlated with leaf area, indicating that the traits were not mutually exclusive. We built simple models by multiple regression to predict early vigour, including some parameters that were easy to measure. Seed mass and leaf width taken together showed better fit than seed mass or leaf width alone. We found a significant coefficient of determination between early vigour in greenhouse and field experiments; thus, screening for early vigour under semi-controlled conditions may be feasible.